High sensitivity measurement of 224Ra and 226Ra in water with an improved hydrous titanium oxide technique at the Sudbury Neutrino Observatory - Aharmim, B; Cleveland, B; Dai, X; Doucas, G; Farine, J; Fergani, H; Ford, R; Hahn, R; Hallman, E; Jelley, N; Lange, R; Majerus, S; et al. (2009)
The existing hydrous titanium oxide (HTiO) technique for the measurement of 224Ra and 226Ra in the water at the Sudbury Neutrino Observatory (SNO) has been changed to make it faster and less sensitive to trace impurities in the HTiO eluate. Using HTiO-loaded filters followed by cation exchange adsorption and HTiO co-precipitation, Ra isotopes from 200 to 450 tonnes of heavy water can be extracted and concentrated into a single sample of a few millilitres with a total chemical efficiency of 50%. Combined with beta-alpha coincidence counting, this method is capable of measuring 1.5 × 10- 3 μ Bq / kg of 224Ra and 3.3 × 10- 3 μ Bq / kg of 226Ra from the 232Th and 238U decay chains, respectively, for a 275 tonne D2 O assay, which are equivalent to 4 × 10- 16 g Th/g and 3 × 10- 16 g U / g in heavy water. © 2009 Elsevier B.V.